Synthesis and structural and morphological characterization of zno2 nanoparticles assisted with UV for bactericidal applications - Colonia, Roberto (2013)
Zinc peroxide (ZnO2) nanoparticles were synthesized by sol-gel technique. The chemicals used for the synthesis were zinc acetate di-hydrate (Zn(CH3COO)2.2H2O) and hydrogen peroxide (H2O2) at 30% under UV radiation. The structure of the ZnO2 nanoparticles was characterized by X-ray diffraction. While the morphology and the cluster size, were determined using scanning electron microscopy. For a preliminary evaluation of the bactericidal properties of the ZnO2, the material was exposed to Bacillus subtilis (ATCC 6051), Escherichia coli (ATCC 25922) y Staphylococcus aureus (ATCC 25923) and it was found that the material has notorious antibacterial activity.